Shuttle plasmids for Escherichia coli and Clostridium perfringens. - Squires, C H (1984)
Small plasmids which replicate in both Escherichia coli and Clostridium perfringens were made by recombining E. coli plasmid pBR322 with three different small (less than 4 kilobases) plasmids native to C. perfringens. Subsequently, two homologous, though distinct, tetracycline resistance determinants (tet) from other C. perfringens plasmids were cloned into them. Both tet systems made E. coli resistant to at least 5 micrograms of tetracycline per ml when resident on the shuttle plasmids. The shuttle vectors have been used to transform L-phase variants and autoplasts of C. perfringens. In the latter case, the intact transforming plasmid could be isolated from walled cells after cell wall regeneration. Reciprocal transformation experiments in which plasmid DNAs derived from E. coli or C. perfringens were used suggest that restriction barriers exist between these two organisms. The plasmids contain restriction enzyme recognition sites in locations which are useful for cloning experiments.